Evaluation of mechanized coffee (Coffea arabica L.) harvest with Ethephon use - Silva, Fábio Moreira da; Souza, Zigomar Menezes de; Arré, Tadeu Jorge; Juan, Rodolfo San; Oliveira, Ezequiel de (Coffee Science - ISSN 1984-3909, 2007)
Coffee harvest mechanization has spread and has become an irreversible process. However, maturation non uniformity is a limiting factor for both mechanical and hand harvesting, because it reduces operational performance and coffee bean quality. Therefore, this work had as objective to study the performance of mechanized harvest on coffee plantations treated with Ethephon, as well as, to evaluate the influence of this product on defoliation and quality of mechanically picked coffee. Three coffee cultivars, with different maturation periods, were used. A completely randomized statistical design, with 40 plants per plot and three replications, was used. Plants were sprayed when indices of fruits at the berry stage, at the upper, medium and lower thirds of the plant, achieved values close to 30%. In relation to fruit maturation in the plants, treatments receiving Ethephon showed an 18% average increase in berry ripening percentage. Mechanical harvesting, held 26 to 34 days after Ethephon applications, resulted on significant increase in percentages and in volume of picked berry. A 46% average increase in picked berry volume was observed. Coffee plant (Coffea arabica L.) defoliation due to mechanized harvest, as well as coffee bean quality were not affected by Ethephon application.